The Use of Laser Therapy for Patients with Fibromyalgia: A Critical Literary Review - Kisselev, Serguei Borisovich; Moskvin, Sergey Vladimirovich (Journal of Lasers in Medical Sciences, 2018)
The management of pain – despite many anaesthetic drugs – remains to be an urgent task. If the goal is to achieve permanent pain relief – and not to temporarily mask the pain (masking pathology) – then this goal can only be achieved by treating pain with physiotherapeutic methods, the most universal and effective of which, is low level laser therapy (LLLT). The treatment methods vary fundamentally in the case of neuropathic (nonspecific, primary) pain, which includes pain with the localization of the trigger points (TP) and nociceptive (specific, secondary), which includes all types of pain resulting from trauma, inflammation, etc. When treating patients with fibromyalgia (FM), a comprehensive approach is required, using different methods of laser therapy and guided by well-known rules. These rules include setting all the correct parameters of the laser exposure (wavelength, operating mode, power, exposure, etc), limiting exposure and power to optimal values and limiting the total time of the procedure and the number of procedures per course.